Synthesis and Gas-Sensing Property of Highly Self-assembled Tungsten Oxide Nanosheets - Hu, Liangbin; Hu, Pengfei; Chen, Yong; Lin, Zehui; Qiu, Changjun (Frontiers in Chemistry, 2018)
We report the synthesis of tungsten oxide (WO3) nanosheets using a simple yet efficient hydrothermal technique free of surfactantand template. The WO3 nano-sheets are self-assembled as well to form ordered one-dimensional chain nanostructure. A comprehensive microscopic characterization reveals that the nano-sheets have triangular and circular two different shape edges, dislocation and stacking faults are also observed, which should have implications for our understanding of catalytic activity of ceria. We also propose a growth mechanism for the nano-sheets. As a result of this unique morphology, this WO3 nano-sheets are found to show excellent gas-sensing properties which can use as promising sensor materials detecting ethanol with low concentration.